Fabrication of p-n Junction Diode Using SnO/SnO2 Thin Films and Its Device Characteristics - Sathyamoorthy, R.; Abhirami, K. M.; Gokul, B.; Gautam, Sanjeev; Chae, Keun Hwa; Asokan, K. (KOREAN INST METALS MATERIALS, 2014)
Present study demonstrates the feasibility of using oxides of Sn to fabricate the p-n junction diode and reports the device characteristics. Reactive thermal evaporation method was used to fabricate the p-type SnO and n-type SnO2 multilayer thin films. The x-ray diffraction (XRD) and Raman spectra depict the presence of both SnO and SnO2 layers. The interface of the p-n junction analyzed by cross-sectional transmission electron microscope (TEM) images and selected area electron diffraction (SAED) pattern confirmed the presence of SnO-SnO2 layers. The diode shows rectifying current-voltage characteristics with forward threshold voltage of 3.5 V.
Keywords: TRANSPARENT CONDUCTING OXIDES; TIN OXIDE; ZNO; EVAPORATION; ELECTRODES; SENSORS; RAMAN; SNO2